Visibility and Effectiveness of PJOK Learning in High Schools in Buleleng District - I Made Subawa Putra Loka; I Ketut Yoda; I Gede Suwiwa (Jurnal Pendidikan Jasmani, Olahraga dan Kesehatan Undiksha, 2024)
Sports and health physical education involves physical activity for students which aims to improve fitness, healthy living behavior and foster sportsmanship. The aim of this research was to determine the visibility and effectiveness of PJOK learning in senior secondary schools (SMA) throughout Buleleng Regency. This type of research is descriptive - quantitative with a sample of 23 schools from a population of 30 schools. By using data collection methods using surveys, observations, documentation studies, interviews and questionnaires. The results of this research show two results in terms of visibility and effectiveness of learning. In terms of visibility, the teacher's personality competency score is 7.66 in the "Good" category, the implementation of learning is 7.55 in the "Good" category, and the learning implementation plan is 7.39 in the "Good" category. , and the ratio of teachers to students is 1: 70.43 in the "Less ideal" category, whereas in terms of learning effectiveness for students' grades, it shows that it is above the minimum completeness criteria value, so students have followed PJOK learning well, as seen from the questionnaire provided given to 75 students with 12 questions giving an overall score of strongly disagree 2.21%, disagree 7% agree 71%, and strongly agree 22%. So it can be concluded in terms of visibility 1) The teacher's personality competency is in the good category by mastering the aspects of being charming, authoritative, the teacher being firm, and samapta, 2) Implementation of good category learning by mastering aspects of opening learning, mastering material, carrying out evaluations, and closing learning, 3) Good category learning implementation plan by mastering aspects of determining learning objectives, designing learning materials, determining learning activity steps, and assessing learning outcomes, 4) The ratio of teachers to students is less than ideal, whereas the effectiveness of learning in delivering material that is easily understood by students, the facilities and infrastructure used are safe and comfortable to use, the learning system is systematic and enjoyable for students, the use of learning media, the learning implementation plan implemented as planned, and students actively participate in the learning provided